Do Children With Dyslexia Have Difficulty In Reading The Quranic Verses Too? - Shalinawati Ramli; Khairani Omar; Mohamad Ahsanullah El Baki; Shahlan Surat (Universiti Sains Islam Malaysia, 2024)
Creative Education, 2016, 7, 1018-1023